2014
DOI: 10.1371/journal.pone.0094686
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Robustness of Network-Based Disease-Gene Prioritization Methods Reveals Redundancy in the Human Interactome and Functional Diversity of Disease-Genes

Abstract: Complex biological systems usually pose a trade-off between robustness and fragility where a small number of perturbations can substantially disrupt the system. Although biological systems are robust against changes in many external and internal conditions, even a single mutation can perturb the system substantially, giving rise to a pathophenotype. Recent advances in identifying and analyzing the sequential variations beneath human disorders help to comprehend a systemic view of the mechanisms underlying vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…We have also retrieved disease-gene associations for these pathologies using DisGeNET, OMIM, and GWAS databases (Menche et al, 2015) (Table 1). The interactome-based proximity (Guney and Oliva, 2014) of NRF2 to known disease genes for each of the NRF2-related disease phenotypes is shown in Fig. 4.…”
Section: B Positioning Nuclear Factor (Erythroid-derived 2)-like 2 Amentioning
confidence: 99%
“…We have also retrieved disease-gene associations for these pathologies using DisGeNET, OMIM, and GWAS databases (Menche et al, 2015) (Table 1). The interactome-based proximity (Guney and Oliva, 2014) of NRF2 to known disease genes for each of the NRF2-related disease phenotypes is shown in Fig. 4.…”
Section: B Positioning Nuclear Factor (Erythroid-derived 2)-like 2 Amentioning
confidence: 99%
“…The robustness of the PPI network used is critical for higher accuracy of these approaches [7982]. Guney and Oliva [83] tested several network-based methods with respect to the perturbations of the system using various disease phenotypes from the Online Mendelian Inheritance in Man (OMIM) database. They found that disease proteins are connected via multiples pathways in a PPI network.…”
Section: Network Metrics Can Identify Disease-associated Proteins In mentioning
confidence: 99%
“…Even when these networks are significantly perturbed, network-based methods can reveal hidden disease association proteins, particularly in cases of breast cancer and diabetes. In general, the PPI network approaches can identify certain proteins associated with specific disease better than the rest [77,83]. …”
Section: Network Metrics Can Identify Disease-associated Proteins In mentioning
confidence: 99%
“…Combined with dynamic nature of interactome [71,72], it is clear that significant work needs to be done to better understand how mutations affect the network and, in turn, how the changes in the interactome, local or global, are associated with the wild type function of the cell. In particular, it is important to take into account the redundancy in the human interactome to prioritize plausible genes involved in a disease [73].…”
Section: Progress Made Inmentioning
confidence: 99%